kontrasten : 22 nederlandse kunstenaars van nu. - Haags Gemeentemuseum, Den Haag (Den Haag : Haags Gemeentemuseum, 1970)
de Bruyn Ouboter, R. ; van Heusden, Wouter ; Escher, M.C. ; Oldeboerrigter, Melle ; Oorthuys, Cas ; Schoonhoven, J.J. ; Nieuwenhuys, Constant A. ; Westerik, Co ; Fieret, Gerard ; van der Heyden, J.C.J. ; Heyboer, Anton ; Veenhuizen, Gerrit ; Snoeck, Jan ; Visser, Carel ; Raaijmakers, D. ; Martens, Peter ; etc.
kontrasten : 22 nederlandse kunstenaars van nu, Haags Gemeentemuseum, Den Haag, 12 september - 15 november 1970
boek